A phytoestrogenic nutraceutical composition from palm leaf extract. - Mohamed, Suhaila (2010)

(untitled)
A comestible composition with phytoestrogenic property against stress, retarding hormone related cancer, affecting fertility and effective to hinder or prevent ailments or conditions resulting from, or exacerbated by, a decrease in endogenous estrogen including reproductive oran ailments, cardiovascular disease, osteoporosis, loss of cognitive function, urinary incontinence, body fat increase, post menopausal syndromes and vasomotor symptoms, and contains extract from palm leaf.